2019
DOI: 10.1097/ta.0000000000002460
|View full text |Cite
|
Sign up to set email alerts
|

Dose optimization of valproic acid in a lethal model of traumatic brain injury, hemorrhage, and multiple trauma in swine

Abstract: BACKGROUND Trauma is a leading cause of death, and traumatic brain injury is one of the hallmark injuries of current military conflicts. Valproic acid (VPA) administration in high doses (300–400 mg/kg) improves survival in lethal trauma models, but effectiveness of lower doses on survival is unknown. This information is essential for properly designing the upcoming clinical trials. We, therefore, performed the current study to determine the lowest dose at which VPA administration improves survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Though we are reluctant to make strong claims on the survival benefit from VPA given the small sample size in this study, previous studies with more power have also demonstrated that VPA can improve survival in swine models of polytrauma and hemorrhagic shock. 6 If a survival difference exists between intravenous and IO administration, this presented work is not adequately powered to detect that difference, and a much larger study would need to be done. Ethical and cost considerations would be prohibitive to doing such a study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Though we are reluctant to make strong claims on the survival benefit from VPA given the small sample size in this study, previous studies with more power have also demonstrated that VPA can improve survival in swine models of polytrauma and hemorrhagic shock. 6 If a survival difference exists between intravenous and IO administration, this presented work is not adequately powered to detect that difference, and a much larger study would need to be done. Ethical and cost considerations would be prohibitive to doing such a study.…”
Section: Discussionmentioning
confidence: 97%
“…The animal protocol and injury pattern has been described in detail previously, and a timeline of the experiment is outlined in figure 1. 6 Briefly, animals underwent placement of femoral venous and arterial lines, a pulmonary artery catheter and open cystostomy for invasive monitoring, hemorrhage and resuscitation. For the injury protocol, animals had a rectus muscle crush injury on one side, femur…”
Section: Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…A stereotactic computer‐controlled cortical impact (CCI) device that is developed by the University of Michigan Innovation Centre is used to induce the TBI. VPA, at the dose of 150 mg kg −1 , is administered via a peripheral intravenous catheter . Details of the model are already published …”
Section: Overview Of Our Tbi Modelmentioning
confidence: 99%
“…VPA has been shown to decrease injury lesion size after TBI, decrease lesion size and improve neurologic recovery after combined TBI and hemorrhagic shock (HS). [5][6][7] Transcriptomic analyses of injured brain tissue and peripheral blood mononuclear cells (PBMCs) demonstrated VPA's efficacy in altering expression of genes critical for determining cell fate. [8][9][10] However, although TBI associated with hemorrhage and polytrauma is a common injury pattern in combat theatres, isolated TBI without extracranial injuries is more common in civilian settings.…”
Section: Introductionmentioning
confidence: 99%